UMPSA students create GebuAdopt, a Digital Platform to support pet adoption process - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 25 August 2025 – The idea for the development of GebuAdopt, a web-based platform to strengthen the pet adoption process in Malaysia, was sparked by observations of the increasing number of stray animals in local communities.